2014
DOI: 10.1080/15389588.2013.843774
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pediatric and Adult Cervical Vertebra—Anatomical Characteristics by Age and Gender for Automotive Application

Abstract: The results obtained in this study help explain variations in cervical anatomical changes associated with age and gender. The information is useful when assessing differences in injury patterns between different segments of the population. Anatomical measurements of the cervical spine should be considered for the development of models used to assess injury mechanisms for various occupant age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
3
18
0
Order By: Relevance
“…; Parenteau et al. ; Yoganandan et al. ), such as higher rates of vertebral fractures and mechanical stress in females due to the smaller size (Gilsanz et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Parenteau et al. ; Yoganandan et al. ), such as higher rates of vertebral fractures and mechanical stress in females due to the smaller size (Gilsanz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the age range of the population was under the 69 year, the possibility of degenerative changes in the vertebra should be considered, which affects the dimensions of the vertebra. Other studies have shown the relationship between age and dimensions of cervical vertebra [4,28].…”
Section: Discussionmentioning
confidence: 99%
“…Analytic morphomics. Individual morphomic parameters were computed as previously described (20)(21)(22)(23)(24)(25). In brief, a custom-built MATLAB-based (The Mathworks Inc., Natick, MA) algorithm was used to identify vertebral elements in a semiautomated manner from Digital Imaging and Communications in Medicine (DICM) files of CT scans.…”
Section: Methodsmentioning
confidence: 99%